Peran Manajemen Talenta, Profesionalisme Anggota, Kualitas Pengawasan Internal, dan Kepuasan Kerja terhadap Kinerja Transformasi Reformasi Polri - Kusprabandaru, Agung; Mayastinasari, Vita (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
The reform of the Indonesian National Police (Polri) requires strengthening organizational performance through the development of human resources as a central pillar. This study analyzes the role of talent management, member professionalism, internal supervision quality, and job satisfaction in supporting the transformation performance of Polri’s reform agenda. Using a qualitative method with a literature review design, this research synthesizes studies from the last ten years, including national and international journals, institutional reports, and official Polri policy documents. The findings reveal that talent management contributes to competency mapping, identification of high-potential personnel, and the establishment of a transparent career system that supports institutional transformation. Member professionalism enhances integrity, technical competence, and adaptability to organizational changes. Internal supervision quality plays a crucial role in ensuring accountability, reducing misconduct, and maintaining public trust. Meanwhile, job satisfaction shapes members’ motivation and commitment to embracing the reform agenda. Overall, these four variables interact to strengthen Polri’s transformation performance, enabling the institution to remain sustainable, adaptive, and service oriented. This study aims to provide theoretical insights and practical recommendations for improving human resource policies and internal control systems within Polri.